1989
DOI: 10.1021/bi00440a009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical events in chloropropionyl-coenzyme A inactivation of acyl-coenzyme A utilizing enzymes

Abstract: Incubation of 3-chloropropionyl-CoA with 3-hydroxy-3-methylglutaryl-CoA synthase results in exchange of the C2 proton with solvent as inactivation of enzyme proceeds. This enzyme is also inhibited by S-acrylyl-N-acetylcysteamine; the limiting rate constant for inactivation by the acrylyl derivative (0.36 min-1) slightly exceeds the value measured for chloropropionyl-CoA (0.31 min-1). These observations support the intermediacy of acrylyl-CoA in the chloropropionyl-CoA-dependent inactivation of hydroxymethylglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Work on yeast [42,43] and avian [44][45][46][47][48][49][50][51] mitochondrial HMG-CoA synthases established that the synthesis of HMG-CoA occurs in three steps. The first, which is rate-limiting, is the acetylation of the enzyme in a cysteinyl thiol group.…”
Section: Mechanism Of Enzyme Reactionmentioning
confidence: 99%
“…Work on yeast [42,43] and avian [44][45][46][47][48][49][50][51] mitochondrial HMG-CoA synthases established that the synthesis of HMG-CoA occurs in three steps. The first, which is rate-limiting, is the acetylation of the enzyme in a cysteinyl thiol group.…”
Section: Mechanism Of Enzyme Reactionmentioning
confidence: 99%
“…(5,6) has demonstrated that cysteine 129 is selectively alkylated by the substrate analog, 3-chloropropionyl-CoA. Additional studies (18) suggest that the process reflects a mechanism-based process, with a general base on the enzyme catalyzing deprotonation of C-2 of the analog's acyl group, a reaction comparable with the deprotonation step that precedes productive condensation between the enzyme's normal substrates. After C-2 of the inhibitor is deprotonated, elimination of chloride and production of acryloylSCoA ensues.…”
Section: Comparison Of Catalysis Of Partial Reactions By Wild Type Anmentioning
confidence: 99%
“…Acryloyl-CoA has been suggested as the inactivating species during 3-chloropropionyl-CoA incubation with HMG-CoA synthase (58) and fatty acid synthase (59). In addition, S-acryloyl-N-acetylcysteamine was shown to inhibit HMG-CoA synthase and lyase and fatty acid synthase (60). However, the data with BTTB-, NPTB-, and DNPTB-CoA clearly show that multiple cycles of generation of this Michael acceptor within the active site of the dehydrogenase does not lead to significant inactivation.…”
Section: Acknowledgmentmentioning
confidence: 99%